MAJELIS TAKLIM KELILING DALAM MEMBINA SIKAP KEAGAMAAN MASYARAKAT - Irawan, Irawan; Nasrudin, Nasrudin; Hermawan, Denny (Universitas Islam Syekh Yusuf, 2019)
AbstarctMajelis taklim is one of the non-formal diniyah educational institutions which aims to increase the faith and piety of Allah SWT and noble morals for its worshipers, as well as manifesting mercy for the universe. In practice, majelis taklim is the most flexible teaching place or Islamic education that is not bound by time. This study aims to reveal data about the role of the Taklim Council in fostering religious attitudes of the community and reveal the inhibiting and supporting factors of the taklim assembly in increasing the practice of community worship. Data collection techniques using questionnaire distribution techniques to the congregation taklim assemblers and observations made to look directly at the reality of the assembly and the objective conditions of the taklim assembly. After the data is collected, the next step is data processing and analysis. For the observational data, logical interpretation is used. The questionnaire result data is used in the percentage scale. The results showed that, the role of the taklim assembly had a low relationship. This can be seen from the correlation coefficient between the variables x and y obtained a correlation value of 0.16 from respondents numbering 40. This means that if interpreted is a very low correlation because it is in the interval 0.00-0.199. Thus proving that the existence of majlis taklim is able to provide religious guidance for the community in improving worship and character of the community with a good attitude category. AbstarkMajelis taklim adalah salah satu lembaga pendidikan diniyah non formal yang bertujuan meningkatkan keimanan dan ketakwaan kepada Allah SWT dan akhlak mulia bagi jamaahnya, serta mewujudkan rahmat bagi alam semesta. Dalam prakteknya, majelis taklim merupakan tempat pengajaran atau pendidikan agama Islam yang paling fleksibel dan tidak terikat oleh waktu. Penelitian ini bertujuan untuk mengungkapkan data tentang peran Majelis taklim dalam membina sikap keagamaam masyarakat dan mengungkap faktor penghambat dan pendukung majelis taklim dalam meningkatkan pengamalan ibadah masyarakat. Teknik pengumpulan data menggunakan teknik penyebaran angket kepada jamaah majelis taklim dan observasi dilakukan untuk melihat langsung terhadap realitas majelis dan kondisi obyektif majelis taklim. Setelah data terkumpul, langkah selanjutnya diadakan pengolahan dan analisa data. Untuk data hasil observasi digunakan penafsiran logika., data hasil angket digunakan skala prosentasi. Hasil penelitian menunjukan bahwa, peranan majelis taklim mempunyai hubungan yang rendah. Hal ini terlihat dari Koefisien korelasi antara variabel x dan y diperoleh nilai korelasi sebesar 0,16 dari responden yang berjumlah 40. Hal ini berarti jika diinterpretasikan merupakan korelasi yang sangat rendah karena berada pada interval 0,00-0,199. Sehingga membuktikan bahwa keberadaan majlis taklim mampu memberikan bimbingan keagamaan bagi masyarakat dalam meningkatkan ibadah dan akhlak masyarakat dengan kategori sikap yang baik.